An Early Diagnosis of an Ovarian Steroid Cell Tumor Not Otherwise Specified in a Woman - Patrícia Alves; Inês Sá; Miguel Brito; Cátia Carnide; Osvaldo Moutinho (Hindawi Limited, 2019)
Steroid cell tumor not otherwise specified is a subtype of steroid ovary tumors. These are a rare subgroup of ovarian sex cord-stromal tumors. We present a case of a young woman submitted to laparoscopic cystectomy with ovarian steroid cell tumor as histological finding. This represents the second case where laparoscopic cystectomy is performed in this type of tumor. Up to 36 months after surgery, the woman remains under surveillance, without recurrence of the tumor, and attempts to conceive. This case suggests that steroid cell tumors can be asymptomatic, and gynecologists must think about preserving fertility in women of reproductive age.